Cell-Peptide Specific Interaction Can Inhibit Mycobacterium tuberculosis H37Rv Infection (2016)
Studying proteins from the M. tuberculosis H37Rv envelop is important for understanding host-pathogen interaction regarding bacterial infection and survival within a host; such knowledge is indispensable regarding studies aimed at developing drugs or vaccines against tuberculosis, a disease which continues to cause more than one million deaths worldwide every year. The present work presents a study of the Rv3705c protein which has been described as being an outer protein. Several servers and bioinformatics' tools were used for predicting its location on mycobacterial surface and a 3D model of the protein was obtained which was then compared to experimental circular dichroism results for its peptides. PCR assays were used for corroborating rv3705c gene presence and transcription in a laboratory strain and immunoblotting and electron microscopy were used for confirming protein localisation on cell envelop. Receptor-ligand assays revealed two peptides having high specific binding (HABPs); peptide 38485 (121DRAFHRVVDRTVGTSGQTTA140) bound to both cell lines used as infection target (U937 and A549 epithelial cell line-derived macrophages) and 38488 (181RLRENVLLQAKVTQSGNAGP200) bound to U937 cells. It was found that peptide 38485 provided significant inhibition regarding mycobacterial entry to both cell lines in in vitro assays. These results led to proposing peptide 38485 as one of the epitopes to be used in future studies aimed at characterising the immune response of functionally important synthetic peptides which could be included in developing a synthetic anti-tuberculosis vaccine. © 2015 Wiley Periodicals, Inc.